Prophetic Politics: Mohammed Arkoun's Rethinking of Islam in Contemporary Politics - Utomo, Wahyu Wiji (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2024)
This article examines Mohammed Arkoun's concept of